Using stealth marketing techniques to increase physical activity and decrease sedentary time in the workplace: a feasibility study investigating the spill-overs of employee pro-environmental behaviour - Manika, D.; Blokland, Y.; Smith, L.; Mansfield, L.; Klonizakis, M. (International Journal of Business Science and Applied Management, 2021)
Sedentary lifestyles have adverse effects on health and wellbeing and are especially prevalent amongst office-based employees. This project goes above and beyond currently existing physical activity initiatives in the workplace, by examining the feasibility of using a "Bait-and-Tease" stealth marketing intervention promoting increased physical activity and reduction of sedentary behaviour in the workplace amongst office-based employees. The intervention focused on promoting employee pro-environmental behaviour in the workplace (i.e., energy saving and recycling). This was the "Bait" part of the technique, which made no reference to physical activity. The spillovers of employee pro-environmental behaviour change on employee physical activity and sedentary behaviour were then evaluated. This was followed by a reveal stage, the "Tease" part of the technique, where the link between health and the environment was made explicit (e.g., taking the stairs instead of the elevator saves energy while also increasing walking time) and participants were informed of the true purpose of the intervention. Initial employee focus groups, grounded on the Behaviour Change Wheel framework, fed into an intervention co-development workshop. The developed intervention, which included an informational campaign and a green champion, was piloted within a Higher Education Institution and targeted academics, professional service members, and postgraduate research students as university employees with office-based jobs. The pilot involved an intervention and a control-group, with a "before" and "after" research design. Both self-reported (i.e., employee surveys measuring pro-environmental behaviour) and observational (i.e., tracking walking and standing time via a mobile application, recording sedentary time and counting stairs via trained observers) data were collected. Results indicate that the intervention was found feasible and the pilot study shows potential for large-scale implementation, even though the pilot sample size was small. The goals of the study were achieved and problems in relation to recruitment, adherence and measurements were identified with multiple future research directions.